2020
DOI: 10.1111/aji.13222
|View full text |Cite
|
Sign up to set email alerts
|

Sestrin2 alleviates palmitate‐induced endoplasmic reticulum stress, apoptosis, and defective invasion of human trophoblast cells

Abstract: Problem Maternal obesity induces elevated saturated fatty acid palmitate levels in the blood and causes pregnancy complications such as gestational diabetes, preeclampsia, fetal growth abnormalities, and stillbirth. Sestrin2, a highly conserved stress‐inducible protein, is involved in the cellular responses of various stress conditions and homeostatic regulation. However, the effects of Sestrin2 on trophoblast cells have not yet been investigated. Here, we investigated the role of Sestrin2 in palmitate‐induced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 49 publications
0
17
0
Order By: Relevance
“…Metabolic dysregulation induces Sestrins as a defense mechanism against obesity and metabolic diseases (Lee et al, 2012;Parmigiani and Budanov, 2016;Dalina et al, 2018). Important key features of cellular function are the regulation of insulin sensitivity, lipid/fatty acid (FA) metabolism, ER stress, and autophagy (Lee et al, 2012(Lee et al, , 2020Park et al, 2014). Glucose starvation, ER stress, amino acid deprivation and mitochondrial dysfunction induces Sestrins as a protective mechanism (Park et al, 2014;Ro et al, 2015;Ye et al, 2015;Ding et al, 2016;Garaeva et al, 2016;Saveljeva et al, 2016).…”
Section: Introduction Of Sestrinsmentioning
confidence: 99%
“…Metabolic dysregulation induces Sestrins as a defense mechanism against obesity and metabolic diseases (Lee et al, 2012;Parmigiani and Budanov, 2016;Dalina et al, 2018). Important key features of cellular function are the regulation of insulin sensitivity, lipid/fatty acid (FA) metabolism, ER stress, and autophagy (Lee et al, 2012(Lee et al, , 2020Park et al, 2014). Glucose starvation, ER stress, amino acid deprivation and mitochondrial dysfunction induces Sestrins as a protective mechanism (Park et al, 2014;Ro et al, 2015;Ye et al, 2015;Ding et al, 2016;Garaeva et al, 2016;Saveljeva et al, 2016).…”
Section: Introduction Of Sestrinsmentioning
confidence: 99%
“…Conversely, overexpressing SESN2 in dendritic cells (DCs) decreased their apoptosis rate and inhibited ER stress‐related protein translation. Consistent with these findings, Lee et al 38 disclosed that SESN2 suppressed impaired trophoblast invasion caused by palmitate and attenuated palmitate‐induced ER stress; conversely, knockdown of SESN2 increased palmitate‐mediated ER stress, inflammatory signalling and apoptosis. Moreover, a recent study proved that glucose starvation caused both energy deficiency and activation of ER stress, in which SESN2 protected cells from glucose starvation‐induced cell death 40 .…”
Section: Sesn2 and Signalling Pathwaysmentioning
confidence: 65%
“…Bruening et al 37 found that the upregulation of SESN2 was associated with the expression of ER stress markers ATF4, ATF3 and C/EBP‐homologous protein (CHOP) in cancer cells. Another study reported that SESN2 inhibited ER stress and inflammation through the AMPK/mTORC1 pathways 38 …”
Section: Sesn2 and Signalling Pathwaysmentioning
confidence: 99%
“…Protein levels of SESN2 are induced upon chronic activation of mTORC1, which subsequently inhibit mTORC1 activation [ 12 , 20 , 24 ]. To evaluate the regulatory effect of SESN2 on the mTORC1 pathway, lentiviral vectors expressing short hairpin RNAs (shRNAs) against human SESN2 or control were transduced into HEC-1A and Ishikawa cells.…”
Section: Resultsmentioning
confidence: 99%
“…Sestrins (SESNs) are a highly conserved protein family comprising SESN1, SESN2, and SESN3 in mammals, and can be induced by various cellular stresses including DNA damage, increased ROS, hypoxia, and ER stress [ 12 , 16 , 17 , 18 ]. SESN2 maintains metabolic homeostasis and prevents age- and obesity-related pathologies by inhibiting ROS accumulation and the mTORC1 pathway [ 12 , 18 , 19 , 20 ]. SESN2 , which is homologous to the SESN1 , is induced by genotoxic and oxidative stresses in a p53-dependent manner [ 19 , 21 ], while SESN2 induction in response to hypoxia and ER stress is p53-independent [ 12 , 22 ].…”
Section: Introductionmentioning
confidence: 99%